Economic evaluations for intensive care unit randomised clinical trials in Australia and New Zealand: Practical recommendations for researchers. Issue 3 (May 2023) - Taylor, Colman B.; Thompson, Kelly J.; Hodgson, Carol; Liew, Cheelim; Litton, Edward; McGain, Forbes; Nichol, Alistair; Rauniyar, Rashmi; Ridley, Emma; Higgins, Alisa
Abstract: Objectives: Economic evaluations of intensive care unit (ICU) interventions have specific considerations, including how to cost ICU stays and accurately measure quality of life in survivors. The aim of this article was to develop best practice recommendations for economic evaluations alongside future ICU randomised controlled trials (RCTs). Review methods: We collated our experience based on expert consensus across several recent economic evaluations to provide best-practice, practical recommendations for researchers conducting economic evaluations alongside RCTs in the ICU. Recommendations were structured according to the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) Consolidated Health Economic Evaluation Reporting Standards (CHEERS) Task Force Report. Results: We discuss recommendations across the components of economic evaluations, including: types of economic evaluation, the population and sample size, study perspective, comparators, time horizon, choice of health outcomes, measurement of effectiveness, measurement and valuation of quality of life, estimating resources and costs, analytical methods, and the increment cost-effectiveness ratio. We also provide future directions for research with regard to developing more robust economic evaluations for the ICU. Conclusion: Economic evaluations should be built alongside ICU RCTs and should be designed a priori using appropriate follow-up and data collection to capture patient-relevant outcomes. Further work is needed to improve the quality of data available for linkage in Australia as well as developing costing methods for the ICU and appropriate quality of life measurements.